Assessment of kinematic concepts comprehension: A systematic review - Akhmad Jufriadi; Sutopo Sutopo; Sentot Kusairi; Sunaryono Sunaryono (International Journal of Evaluation and Research in Education (IJERE), 2023)
A systematic study on the development of the assessment instrument of the concept of kinematics which is one of the basic concepts of physics has not yet been conducted. This systematic study reported the characteristics, quality, effectiveness, and efficiency of the instrument assessment regarding the concept of kinematics. This systematic review method has used a systematic approach based on the practical guidelines of systematic reviews by Petticrew and Roberts and has used PRISMA diagrams for the process of searching and selecting articles, who reviewed 12 articles published between 1985 and 2021. The research findings show that the instrument of concept mastery of kinematics using multiple-choice formats, while others combine the true-false and multiple-choice formats. Almost all instruments of mastery of the concept of widely used kinematics have reported validity assessment (content validity, construct validity) and internal consistency reliability. However, predictive validity, discriminatory validity, and temporal stability reliability have not been reported. Other results indicate that the development of further assessments must pay attention to five important aspects: the validity and reliability of instruments, the scopes and specificity of the concept of kinematics, the conformity with the intellectual level of students, the effectiveness and efficiency of instrument assessment, and the fulfillment of research gaps. This study can help educators and researchers choose and develop an appropriate instrument assessment to reveal students’ understanding of the concept of kinematics.